A high-frequency EPR study of magnetic anisotropy and intermolecular interactions of Co(II) ions - Spillecke, Lena; Tripathi, Shalini; Koo, Changhyun; Ansari, Mursaleem; Vaidya, Shefali; Rasamsetty, Amaleswari; Mallah, Talal; Rajaraman, Gopalan; Shanmugam, Maheswaran; Klingeler, Rüdiger (Polyhedron, 2021)
Changing the anion in a crystal lattice induces distinct structural distortions in the [CoS4]2+ core for a family of complexes with the general molecular formula [Co(L1)4]X2, where L1 = thiourea (NH2CSNH2) and X = I (1), Br (2), and [Co(L1)4](SiF6) (3). The magnetic anisotropy (D) for 1-3 was quantitatively determined with a magnitude of −153(2), −168(5) and < -400 GHz, respectively, by HF-EPR investigation. Also, intermolecular exchange interactions were determined experimentally, whereby an antiferromagnetic exchange for 1 (-5.5 GHz) and 2 (-4.1 GHz), and a ferromagnetic interaction for 3 (+3.5 GHz) are witnessed (based on H = -JS1S2). The exchange interactions, computed using DFT methods on a model complex of 1, disclose the presence of an antiferromagnetic exchange interaction, consistent with the experimental observation. Overall, the present study provides convincing experimental evidence for the sizable influence not only of the first but also of the second coordination sphere on the magnetic anisotropy and exchange interactions of Co(II) ions.
Gesehen am 04.11.2021